A new species of Dolichopoda (Orthoptera: Rhaphidophoridae; Dolichopodainae) from Western Greece - Russo, Claudio Di; Alexiou, Sotiris; Rampini, Mauro (Zootaxa, 2017)
In this paper we report the description of a new species, Dolichopoda bakolitsasi, from a cave of Mount Thiamon in Aetolia-Acarnania (Western Greece). The new species shows some affinity with the geographically close D. giachinoi Rampini & Di Russo, 2008 and the other Southern Ionian species from which it differs mainly by the shape of the two lobes of the male tenth (X) tergite. This character, in fact, is very peculiar and unique in the whole genus, with the lobes being forceps-shaped distally, with the apex curved inwards. The new species has no morphological affinities with D. lustriae Rampini & Di Russo, 2008, a species inhabiting caves of the eastern slopes of the nearby Mount Valtou. The co-occurrence at the same area of two well separated, unrelated species, is discussed in relation to the present and past geographical scenario of this area of the Western Greece.